Impaired response of memory Treg to high density lipoproteins is associated with intermediate/high cardiovascular disease risk in persons with HIV - Atehortua, Laura; Baig, Mirza; Morris, Jamie; Trentman, Sarah; Davidson, W. Sean; Fichtenbaum, Carl J.; Chougnet, Claire A. (Frontiers in Immunology, 2023)
Cardiovascular disease (CVD) is a leading cause of enhanced morbidity and mortality in persons with HIV (PWH) in the era of highly active antiretroviral therapy (AART). However, the underlying mechanisms are not fully understood. Regulatory T cells (Treg), notably the highly suppressive memory subset, have been shown to limit CVD. Importantly, memory Treg cell numbers remain low in many treated PWH. High density lipoproteins (HDL) also protect from CVD, and we previously found that Treg-HDL interactions reduce oxidative stress in these cells. Here, we evaluated Treg-HDL interactions in PWH and whether they were operative in those higher CVD risk. To do that, we recruited a cohort of PWH with intermediate/high CVD risk (median ASCVD risk score of 13.2%, n=15) or low/borderline risk (median ASCVD risk score of 3.6%, n=14), as well as a group of statins treated PWH with intermediate/high CVD risk (median ASCVD risk score of 12.7%, n=14). We evaluated Treg frequency, phenotype and response to HDL. PWH with Int/High CVD risk had a significantly lower number of memory Treg, but memory Treg were more activated and displayed an inflammatory phenotype, versus those with Low/BL CVD risk. In untreated patients, Treg absolute numbers were negatively correlated with ASCVD score. Although HDL decreased oxidative stress in memory Treg in all subjects, memory Treg from PWH with Int/High CVD risk were significantly less responsive to HDL than those from PWH with Low/BL CVD risk. The level of oxidative stress in memory Treg positively correlated with ASCVD scores. In contrast, plasma HDL from PWH, regardless of CVD risk, retained their anti-oxidative properties, suggesting that the defect in memory Treg response to HDL is intrinsic. Statin treatment partially ameliorated the memory Treg defect. In conclusion, the defective HDL-Treg interactions may contribute to the inflammation-induced increased CVD risk observed in many AART-treated PWH